The Effect of Training on Work Productivity of PDAM Tirta Kampar - Mifta Hasda; Zubaidah Assyifa; Rifqil Khairi (Global Sustainability Research Institute, 2024)
Introduction: This research aims to evaluate the impact of training on employee work productivity at PDAM Tirta Kampar. Methods: This research uses a quantitative approach with simple linear regression as the analysis method. Research data was collected through a survey of PDAM Tirta Kampar employees which was conducted offline and after data screening a sample of 35 respondents was obtained which could be used in the research. Results: The research results show a significant increase in employee work productivity after participating in the training. This is reflected in increased operational efficiency, more optimal management of water resources, and improved services to the community. The analysis also shows increased employee motivation and job satisfaction, creating a more productive work environment. Conclusion and suggestion: This research provides an overview of management in integrating training concepts in the context of daily work, and the use of effective evaluation mechanisms to continue to support human resource development through targeted and planned training while ensuring continuous efforts in monitoring and evaluating its impact on the productivity and overall well-being of the organization.